Ratio of hemoglobin to red cell distribution width: an inflammatory predictor of survival in AIDS-related DLBCL - Chen, Juanjuan; Wu, Yihua; Zhao, Han; Ruan, Guangjing; Qin, Shanfang (Frontiers in Immunology, 2024)
Background: Despite the introduction of combined antiretroviral therapy, AIDS-related diffuse large B-cell lymphoma (AR-DLBCL) remains a prominent cancer among individuals living with HIV with a suboptimal prognosis. Identifying independent prognostic markers could improve risk stratification. Methods: In this multicenter retrospective cohort study spanning years 2011 to 2019, 153 eligible patients with AR-DLBCL were examined. Overall survival (OS) factors were analyzed using Kaplan–Meier curves, and univariate and multivariate Cox proportional hazards models. The discriminatory ability of the risk score was evaluated by examining the area under the receiver operating characteristic curve. Results: The study included 153 patients with a median age of 47 years (interquartile range [IQR] 39–58), 83.7% of whom were men. The median follow-up was 12.0 months (95% confidence interval [CI], 8.5–15.5), with an OS rate of 35.9%. Among the potential inflammatory markers examined, only the ratio of hemoglobin (g/dL) to red cell distribution width (%) (Hb/RDW) emerged as an independent prognostic parameter for OS in the training (hazard ratios [HR] = 2.645, 95% CI = 1.267–5.522, P = 0.010) and validation cohorts (HR = 2.645, 95% CI = 1.267–5.522, P = 0.010). A lower Hb/RDW ratio was strongly correlated with adverse clinical factors, including advanced Ann Arbor stage, increased extranodal sites, reduced CD4 count, elevated lactate dehydrogenase levels, poorer Eastern Cooperative Oncology Group performance status (ECOG PS), and a higher International Prognostic Index (IPI) score. The addition of the Hb/RDW ratio to the IPI produced a highly discriminatory prognostic composite score, termed Hb/RDW-IPI. Conclusions: We identified a cost-effective and readily available inflammatory biomarker, the Hb/RDW ratio, as an independent predictor of outcomes in patients with AR-DLBCL. Its integration into the IPI score partially improves prognostic accuracy.